Catalyst and preparation method and application thereof, dehydrogenation method of hydrogen storage carrier
By developing a catalyst with a core-shell structure, using the core of non-precious metals, metals and additives and the shell of noble metal active components, the problem of side reactions in the dehydrogenation process in organic liquid hydrogen storage technology is solved, and a higher dehydrogenation rate, stability and number of recycled use of hydrogen storage carriers are achieved.
Patent Information
- Application Number
- CN202411670919.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing organic liquid hydrogen storage technology is prone to side reactions between catalysts and hydrogen storage carriers during the dehydrogenation process, resulting in impurities being mixed into the product, increasing the difficulty of hydrogen purification, and affecting the structural stability and number of cycles of hydrogen storage carriers.
A catalyst with a core-shell structure is developed, the inner core includes non-precious metals, metals and additives supported on the support, and the outer shell includes an alumina cladding layer and a precious metal active component supported on the alumina cladding layer. By regulating the distribution position of the active component, the coordination of the catalyst is optimized to reduce the occurrence of side reactions of the hydrogen storage support.
While obtaining a higher dehydrogenation rate, the occurrence of side reactions of hydrogen storage support is effectively suppressed, and the service life of the catalyst, the stability and number of cycles of hydrogen storage support are improved.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a catalyst and a preparation method and application thereof, and a dehydrogenation method of a hydrogen storage carrier. Background Art
[0002] With the growing global demand for clean energy, hydrogen, as a green fuel and energy carrier with great potential, is becoming increasingly important, especially hydrogen produced from renewable energy such as solar or wind power. In my country, photovoltaic power generation technology and water electrolysis hydrogen production technology are already quite mature, providing a solid foundation for the large-scale production of hydrogen. However, the widespread use of hydrogen still faces a major challenge, that is, how to store and transport hydrogen safely and efficiently.
[0003] At present, high-pressure gaseous hydrogen storage technology is the most mature hydrogen storage method for commercial application, and its operation is simple and convenient. However, this technology has significant limitations, such as high storage pressure (usually in the range of 35-70MPa), which not only places extremely stringent requirements on the material and design of hydrogen storage tanks, but also increases the difficulty of transportation and storage, which is not conducive to the large-scale application of hydrogen. On the other hand, although cryogenic liquid hydrogen storage technology has an extremely high hydrogen storage density, the preparation of liquid hydrogen requires extremely low temperatures (below -253°C), which is accompanied by huge energy consumption, significantly increasing the economic cost and limiting its commercialization process.
[0004] In response to the above problems, chemical hydrogen storage technology, especially organic liquid hydrogen storage technology, has attracted much attention due to its unique advantages. This technology uses organic matter containing unsaturated bonds as hydrogen storage carriers to achieve hydrogen storage and release through hydrogenation and dehydrogenation reactions. Compared with other hydrogen storage methods, organic liquid hydrogen storage technology has the advantages of high hydrogen storage density, low cost, good compatibility with existing infrastructure, and safe transportation at normal temperature and pressure. Therefore, it is widely recommended as one of the ideal choices for hydrogen storage and transportation.
[0005] However, the current development of organic liquid hydrogen storage technology still faces some technical bottlenecks. First, during the dehydrogenation process, commonly used hydrogen storage carriers such as dibenzyltoluene, toluene, 12H-nitroethylcarbazole, etc. are prone to side reactions between catalysts and hydrogen storage carriers, resulting in the mixing of impurities such as methane and ethane into the product hydrogen, which increases the difficulty of hydrogen purification and may damage the structure of the hydrogen storage carrier, affecting its cycle stability.
[0006] Therefore, developing a new dehydrogenation catalyst, optimizing the dehydrogenation reaction conditions, and reducing the generation of dehydrogenation by-products are of great significance for promoting the commercial application of organic liquid hydrogen storage technology and promoting the rapid development of the hydrogen energy industry. Summary of the invention
[0007] The purpose of the present invention is to overcome the problem of side reactions between the catalyst and the hydrogen storage carrier in the dehydrogenation process of the hydrogen storage carrier in the prior art, and to provide a catalyst and its preparation method and application, and a dehydrogenation method for the hydrogen storage carrier. The catalyst can effectively inhibit the occurrence of side reactions of the hydrogen storage carrier while obtaining a higher dehydrogenation rate.
[0008] In order to achieve the above object, the present invention provides a catalyst in a first aspect, wherein the catalyst has a core-shell structure, including a core and an outer shell, wherein the core includes a carrier and a non-precious metal, a co-metal and an auxiliary agent supported on the carrier, and the outer shell includes an alumina coating layer and a precious metal active component supported on the alumina coating layer;
[0009] Wherein, the non-precious metal includes Ni;
[0010] The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals;
[0011] The auxiliary agent is S and / or P.
[0012] A second aspect of the present invention provides a method for preparing a catalyst, comprising the following steps:
[0013] (1) impregnating a carrier with an impregnation solution containing a non-precious metal precursor, a metal promoter precursor and an additive precursor, and then drying and first calcining the carrier to obtain a core of the catalyst;
[0014] (2) contacting the inner core of the catalyst obtained in step (1) with a mixed solution containing an alumina precursor, and then performing a second calcination to obtain a catalyst precursor having a core-shell structure;
[0015] (3) impregnating the catalyst precursor obtained in step (2) with a mixed solution containing a noble metal active component, and performing a reduction treatment to obtain the catalyst;
[0016] Wherein, the non-precious metal includes Ni;
[0017] The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals;
[0018] The auxiliary agent is S and / or P.
[0019] The third aspect of the present invention provides a catalyst prepared by the preparation method described in the second aspect.
[0020] The fourth aspect of the present invention provides an application of the catalyst described in the first aspect or the third aspect in the field of hydrogen storage.
[0021] A fifth aspect of the present invention provides a method for dehydrogenating a hydrogen storage carrier, comprising: contacting the hydrogen storage carrier with a dehydrogenation catalyst under dehydrogenation conditions;
[0022] Wherein, the dehydrogenation catalyst is the catalyst described in the first aspect or the third aspect.
[0023] Through the above technical scheme, the catalyst provided by the present invention has a core-shell structure, and by regulating the distribution positions of the active components in the catalyst on the inner core and the outer shell, the non-precious metal, the co-metal, the auxiliary agent and the precious metal active components can play a good coordination role: ① the catalyst can effectively reduce the residence time of the hydrogen storage carrier in the inner core while obtaining a higher dehydrogenation rate, thereby reducing the influence of internal diffusion on the side reactions of the catalyst and the hydrogen storage carrier, and improving the service life of the catalyst; ② reducing the breakage of the CC bond and / or CN in the hydrogen storage carrier, and finally achieving the suppression of the occurrence of the side reactions of the hydrogen storage carrier during the dehydrogenation process, and improving the stability and recycling number of the hydrogen storage carrier.
[0024] Preferably, the present invention further limits the types and / or contents of non-precious metals, co-metals, additives and precious metal active components, so that the catalyst can obtain a better dehydrogenation rate while better suppressing the occurrence of side reactions of the hydrogen storage carrier, thereby further improving the problems of unstable hydrogen storage carrier structure, low number of recycling times and excessively high dehydrogenation cost caused by side reactions. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] The first aspect of the present invention provides a catalyst, wherein the catalyst has a core-shell structure, including a core and an outer shell, wherein the core includes a carrier and a non-precious metal, a co-metal and an auxiliary agent supported on the carrier, and the outer shell includes an alumina coating layer and a precious metal active component supported on the alumina coating layer;
[0027] Wherein, the non-precious metal includes Ni;
[0028] The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals;
[0029] The auxiliary agent is S and / or P.
[0030] The catalyst provided by the present invention has a core-shell structure. By regulating the distribution positions of the active components in the catalyst on the inner core and the outer shell, the non-precious metal, the auxiliary metal, the auxiliary agent and the precious metal active components can play a good coordination role, so that the catalyst can effectively reduce the residence time of the hydrogen storage carrier in the inner core while obtaining a higher dehydrogenation rate, further reduce the influence of the side reaction of the internal diffusion hydrogen storage carrier, and improve the service life of the catalyst; and reduce the breakage of the CC bond and / or CN in the hydrogen storage carrier, finally realizing the suppression of the occurrence of the side reaction of the hydrogen storage carrier during the dehydrogenation process, and improving the stability and the number of cycles of the hydrogen storage carrier.
[0031] In the present invention, the range of the carrier type is relatively wide, and those skilled in the art can select it according to actual needs. Preferably, the carrier is selected from at least one of aluminum oxide, silicon oxide and titanium oxide, and more preferably aluminum oxide.
[0032] According to a particularly preferred embodiment of the present invention, the VIB Group metal is Cr and / or Mo, preferably Cr.
[0033] According to a particularly preferred embodiment of the present invention, the Group VIIB metal is Mn and / or Tc, preferably Mn.
[0034] The use of the above preferred types of VIB group and / or VIIB group metals can achieve better coordination between the auxiliary metal and the non-precious metal and the auxiliary agent, thereby better improving the dehydrogenation rate while more effectively suppressing the occurrence of side reactions of the hydrogen storage carrier.
[0035] According to a particularly preferred embodiment of the present invention, the auxiliary agent is S.
[0036] According to a particularly preferred embodiment of the present invention, the noble metal active component is selected from at least one of Pd, Pt, Au, and Ag, preferably Pd and / or Pt, and more preferably Pd.
[0037] According to a particularly preferred embodiment of the present invention, based on the total amount of the catalyst, the content of non-precious metals calculated as elements is 5-35wt%, the content of auxiliary metals calculated as elements is 0.5-6wt%, and the content of auxiliary agents calculated as elements is 0.1-1wt%; preferably, based on the total amount of the catalyst, the content of non-precious metals calculated as elements is 10-16wt%, the content of auxiliary metals calculated as elements is 1-5.5wt%, and the content of auxiliary agents calculated as elements is 0.2-0.5wt%. The use of non-precious metals, auxiliary metals and auxiliary agents within the above preferred content range is conducive to a better coordination effect between the three, thereby better improving the dehydrogenation rate while more effectively suppressing the occurrence of side reactions of hydrogen storage carriers.
[0038] According to a particularly preferred embodiment of the present invention, when the auxiliary metal is a VIB group metal element, the content of the auxiliary metal calculated as the element is 1-6 wt %, more preferably 1.5-5.5 wt %, based on the total amount of the catalyst.
[0039] According to a particularly preferred embodiment of the present invention, when the auxiliary metal is a metal element of Group VIIB, the content of the auxiliary metal calculated as the element is 0.5-5wt%, more preferably 1-3wt%, based on the total amount of the catalyst.
[0040] The use of the above-mentioned preferred content of VIB group and / or VIIB group metal is more conducive to strengthening the coordination between the auxiliary metal and the non-precious metal and the auxiliary agent, thereby further effectively suppressing the occurrence of side reactions of the hydrogen storage carrier while improving the dehydrogenation rate.
[0041] In the present invention, the diameter of the core has a wide range of choices, and those skilled in the art can make a choice according to actual needs. Preferably, the diameter of the core is 2.5-3.5 mm.
[0042] According to a particularly preferred embodiment of the present invention, based on the total amount of the catalyst, the thickness of the alumina coating layer is 0.08-0.25 mm, preferably 0.1-0.2 mm. The alumina coating layer with the above preferred thickness can make the catalyst have a core-shell structure while making the non-precious metal, auxiliary metal and auxiliary agent loaded on the carrier have a better catalytic effect, thereby better improving the dehydrogenation rate of the catalyst and reducing the occurrence of side reactions of the hydrogen storage carrier during the catalytic process.
[0043] In the present invention, the core diameter and the thickness of the alumina coating layer are measured using a scanning electron microscope.
[0044] According to a particularly preferred embodiment of the present invention, the ratio of the inner core radius to the alumina coating layer is 6.5-20: 1, preferably 8-15: 1. The ratio within the above preferred range can achieve a better coordination effect between the non-precious metal, auxiliary metal and auxiliary agent loaded on the carrier and the precious metal active component loaded on the alumina coating layer, thereby better improving the dehydrogenation rate and reducing the occurrence of side reactions of the hydrogen storage carrier.
[0045] According to a particularly preferred embodiment of the present invention, based on the total amount of the catalyst, the content of the noble metal active component is 0.01-0.5wt%, more preferably 0.15-0.4wt%. The above preferred content of the noble metal active component can better improve the dehydrogenation rate and reduce the occurrence of side reactions of the hydrogen storage carrier.
[0046] In the present invention, the contents of the non-precious metals, auxiliary metals, auxiliary agents and precious metals are mainly measured by ICP analysis, wherein the S content is measured by a sulfur-carbon analyzer.
[0047] A second aspect of the present invention provides a method for preparing a catalyst, comprising the following steps:
[0048] (1) impregnating a carrier with an impregnation solution containing a non-precious metal precursor, a metal promoter precursor and an additive precursor, and then drying and first calcining the carrier to obtain a core of the catalyst;
[0049] (2) contacting the inner core of the catalyst obtained in step (1) with a mixed solution containing an alumina precursor, and then performing a second calcination to obtain a catalyst precursor having a core-shell structure;
[0050] (3) impregnating the catalyst precursor obtained in step (2) with a mixed solution containing a noble metal active component, and performing a reduction treatment to obtain the catalyst;
[0051] Wherein, the non-precious metal includes Ni;
[0052] The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals;
[0053] The auxiliary agent is S and / or P.
[0054] In the preparation method described in the second aspect of the present invention, the selection range of the types of the carrier, non-precious metal, co-metal, auxiliary agent and precious metal active component is the same as the selection range described in the first aspect above, and the present invention will not be repeated here.
[0055] In the present invention, the concentration of the impregnation solution containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor in step (1) and the type of solvent can be selected in a wide range, as long as the loading of the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor can be achieved, and those skilled in the art can make the selection according to actual needs.
[0056] In the present invention, the type of solute in the impregnation solution containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor in step (1) has a wide selection range, as long as the loading of the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor can be achieved, and the technicians in this field can make a selection according to actual needs. Preferably, the solute is a soluble non-precious metal salt, a soluble co-metal salt and an acid and / or acid salt containing an auxiliary agent. Among them, the acid and / or acid salt containing an auxiliary agent is preferably at least one of sulfuric acid, ammonium sulfate, phosphoric acid and diammonium hydrogen phosphate.
[0057] In the present invention, the range of selection for the impregnation method of step (1) is relatively wide, as long as the loading of the non-precious metal precursor, the metal precursor and the auxiliary agent precursor can be achieved, and the technicians in this field can make a selection according to actual needs. Preferably, the impregnation method is equal volume impregnation. The conditions for the impregnation of the present invention have a wide range of selection. Preferably, the conditions for the impregnation include: impregnation at room temperature (25±5°C) for 2-4h.
[0058] In the present invention, the selection range of the carrier type in step (1) is relatively wide, and those skilled in the art can select it according to actual needs. Preferably, the carrier is selected from at least one of aluminum oxide, silicon oxide and titanium oxide, and more preferably aluminum oxide. In the present invention, the carrier is preferably a shaped carrier, and the diameter of the carrier has a relatively wide selection range. Preferably, the diameter of the carrier is 2.5-3.5 mm.
[0059] According to a particularly preferred embodiment of the present invention, in step (1), the amount of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor is such that, based on the total amount of the prepared catalyst, the content of the non-precious metal calculated as an element is 5-35wt%, the content of the co-metal calculated as an element is 0.5-6wt%, and the content of the auxiliary agent calculated as an element is 0.1-1wt%; more preferably, the content of the non-precious metal calculated as an element is 10-16wt%, the content of the co-metal calculated as an element is 1-5.5wt%, and the content of the auxiliary agent calculated as an element is 0.2-0.5wt%. The use of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor within the above preferred dosage range can make the non-precious metal, the co-metal and the auxiliary agent have a better coordination effect, thereby better improving the dehydrogenation rate while more effectively reducing the occurrence of side reactions of the hydrogen storage carrier.
[0060] According to a particularly preferred embodiment of the present invention, when the co-metal is a metal element of Group VIB, the amount of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor is such that, based on the total amount of the prepared catalyst, the content of the co-metal in terms of element is 1-6wt%, more preferably 1.5-5.5wt%. The use of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor within the above preferred dosage range can further strengthen the coordination between the co-metal and the non-precious metal and the auxiliary agent, thereby further effectively suppressing the occurrence of the side reaction of the hydrogen storage carrier while further improving the dehydrogenation rate.
[0061] According to a particularly preferred embodiment of the present invention, when the co-metal is a metal element of Group VIIB, the amount of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor is such that, based on the total amount of the prepared catalyst, the content of the co-metal in terms of element is 0.5-5wt%, more preferably 1-3wt%. The use of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor within the above preferred dosage range can further strengthen the coordination between the co-metal and the non-precious metal and the auxiliary agent, thereby further effectively reducing the occurrence of side reactions of the hydrogen storage carrier while further improving the dehydrogenation rate.
[0062] According to a particularly preferred embodiment of the present invention, the drying conditions include: a drying temperature of 80-200° C., preferably 90-150° C., and a drying time of 2-24 h, preferably 2-12 h.
[0063] According to a particularly preferred embodiment of the present invention, the first calcination conditions include: a calcination temperature of 350-600° C., preferably 400-550° C., and a calcination time of 2-12 h, preferably 2-6 h.
[0064] In the present invention, the inner core diameter of the catalyst prepared in step (1) has a wide range of choices, and those skilled in the art can select it according to actual needs. Preferably, the inner core diameter is 2.5-3.5 mm.
[0065] In the present invention, the concentration of the mixed solution containing the aluminum oxide precursor and the type of solvent in step (2) can be selected in a wide range, as long as the aluminum oxide coating layer can be prepared. Preferably, the concentration of the mixed solution containing the aluminum oxide precursor is 5-35wt%, preferably 5-20wt%.
[0066] In the present invention, the alumina precursor in step (2) has a wide range of choices, as long as the alumina coating layer can be obtained through the subsequent second calcination, and those skilled in the art can make the selection according to actual needs. Preferably, the alumina precursor is pseudo-boehmite.
[0067] In the present invention, the contacting method has a wide range of choices, as long as the coating of the inner core can be achieved, and the technicians in this field can make a choice according to actual needs. Preferably, the contacting method is air blast coating. In the present invention, the air blast coating is preferably carried out in an air blast coating machine. The contacting conditions of the present invention have a wide range of choices, as long as the alumina precursor can be loaded on the inner core surface of the catalyst and an alumina coating layer of the desired thickness can be obtained. Preferably, the contacting conditions include: a temperature of 50-80°C and a time of 10-40min.
[0068] According to a particularly preferred embodiment of the present invention, the amount of the mixed solution containing the alumina precursor is such that, based on the total amount of the prepared catalyst, the thickness of the alumina coating layer is 0.08-0.25 mm, preferably 0.1-0.2 mm. The adoption of the alumina coating layer of the above preferred thickness enables the prepared catalyst to have a core-shell structure while enabling the non-precious metal, co-metal and auxiliary agent loaded on the carrier to have a better catalytic effect, thereby better improving the dehydrogenation rate of the catalyst and reducing the occurrence of side reactions of the hydrogen storage carrier.
[0069] According to a particularly preferred embodiment of the present invention, the conditions for the second calcination include: a calcination temperature of 350-600° C., preferably 450-500° C., and a calcination time of 2-12 h, preferably 2-4 h.
[0070] In the present invention, the concentration of the mixed solution containing the precious metal active component in step (3) and the type of solvent can be selected in a wide range, as long as the precious metal active component can be loaded on the surface of the alumina coating layer. Those skilled in the art can make the selection according to actual needs.
[0071] In the present invention, the solute type of the mixed solution containing the precious metal active component in step (3) can be selected in a wide range, as long as the precious metal active component can be loaded on the surface of the alumina coating layer, and those skilled in the art can select it according to actual needs. Preferably, the solute of the mixed solution containing the precious metal active component is a soluble precious metal salt.
[0072] In the present invention, the range of selection of the impregnation method and conditions of step (3) is relatively wide, as long as the loading of the noble metal active component on the surface of the alumina coating layer can be achieved, and those skilled in the art can make a selection according to actual needs. Preferably, the impregnation method is equal volume impregnation. The conditions of the impregnation described in the present invention have a relatively wide range of selection. Preferably, the conditions of the impregnation include: impregnation at room temperature (25±5°C) for 2-4h.
[0073] In the present invention, preferably, the method of step (3) further comprises: drying the catalyst precursor obtained in step (2) after impregnation. The drying conditions of the present invention are not particularly limited. Preferably, the drying temperature is 80-200°C, preferably 90-150°C, and the drying time is 2-24h, preferably 2-12h.
[0074] In the present invention, unless otherwise specified, the effect of the preparation process in step (3) on the thickness of the catalyst shell can be ignored.
[0075] According to a particularly preferred embodiment of the present invention, in the prepared catalyst, the ratio of the core radius to the thickness of the alumina coating layer is 6.5-20: 1, preferably 8-15: 1. The ratio within the above preferred range can achieve a better coordination effect between the non-precious metal, co-metal and auxiliary agent loaded on the carrier and the precious metal active component loaded on the alumina coating layer, thereby better improving the dehydrogenation rate and reducing the occurrence of side reactions of the hydrogen storage carrier.
[0076] According to a particularly preferred embodiment of the present invention, the amount of the mixed solution containing the precious metal active component is such that, based on the total amount of the prepared catalyst, the content of the precious metal active component is 0.01-0.5wt%, more preferably 0.15-0.4wt%. The precious metal active component content within the above range can better improve the dehydrogenation rate and reduce the occurrence of side reactions of the hydrogen storage carrier.
[0077] According to a particularly preferred embodiment of the present invention, the reduction treatment conditions include: in a hydrogen-containing atmosphere, the reduction temperature is 250-600° C., preferably 300-450° C., and the reduction time is 2-12 h, preferably 2-6 h.
[0078] The third aspect of the present invention provides a catalyst prepared by the preparation method described in the second aspect.
[0079] In the present invention, the catalyst has all the technical features of the catalyst described in the first aspect above, which will not be described in detail here.
[0080] The fourth aspect of the present invention provides an application of the catalyst described in the first aspect or the third aspect in the field of hydrogen storage, preferably in the field of organic liquid hydrogen storage.
[0081] In the present invention, the catalyst is particularly suitable for use in the field of organic liquid hydrogen storage, so as to achieve a better dehydrogenation rate while better suppressing the occurrence of side reactions of the hydrogen storage carrier.
[0082] A fifth aspect of the present invention provides a method for dehydrogenating a hydrogen storage carrier, comprising: contacting the hydrogen storage carrier with a dehydrogenation catalyst under dehydrogenation conditions;
[0083] Wherein, the dehydrogenation catalyst is the catalyst described in the first aspect or the third aspect.
[0084] The present invention has a wide range of selection conditions for the dehydrogenation. Preferably, the dehydrogenation conditions include: a temperature of 150-350°C, preferably 160-260°C, a pressure of 0.05-0.2MPa, preferably 0.09-0.12MPa, and a reaction volume space velocity of 0.2-4h -1 , preferably 0.2-2h -1 .
[0085] According to a particularly preferred embodiment of the present invention, the hydrogen storage carrier is an organic liquid hydrogen storage carrier.
[0086] In the present invention, the selection range of the organic liquid hydrogen storage carrier is relatively wide, and conventional organic liquid hydrogen storage carriers in the art are all suitable for the dehydrogenation method provided by the present invention. Preferably, it is a hydrogenated nitrogen-containing heterocyclic organic liquid hydrogen storage carrier, and more preferably, it is selected from at least one of hydrogenated carbazole, N-ethyl carbazole, N-propyl carbazole, N-butyl carbazole and indole.
[0087] According to a particularly preferred embodiment of the present invention, the organic liquid hydrogen storage medium is hydrogenated N-ethylcarbazole. In the above preferred case, it is more conducive to improving the hydrogen production efficiency.
[0088] The present invention will be described in detail below through examples.
[0089] In the present invention, the contents of the non-precious metals, auxiliary metals, auxiliary agents and precious metals are mainly measured by ICP analysis, wherein the S content is measured by a sulfur-carbon analyzer.
[0090] Example 1
[0091] (1) dissolving 39.64 g of nickel nitrate hexahydrate, 7.7 g of chromium nitrate nonahydrate and 0.47 g of sulfuric acid in 40 mL of deionized water to obtain an impregnation solution;
[0092] (2) adding 40.2 g of an alumina carrier having a diameter of 3 mm to the impregnation solution obtained in step (1), impregnating the solution at 25° C. for 2 h, and then placing the solution in a rotary evaporation container and drying the solution at 120° C. for 2 h;
[0093] (3) placing the material obtained in step (2) into a muffle furnace and calcining at 450° C. for 3 h to obtain a catalyst core;
[0094] (4) contacting the catalyst core obtained in step (3) with 50 mL of pseudo-boehmite slurry (concentration of 10.5 wt%) in a blower coater at 70° C. for 30 min to coat the surface of the catalyst core with pseudo-boehmite, and then calcining at 450° C. for 4 h, so that the surface of the catalyst core is coated with an alumina coating layer with a thickness of 0.15 mm;
[0095] (5) then dissolving 0.54 g of a palladium nitrate solution having a concentration of 18.56 wt % in 40 mL of deionized water to obtain an impregnation solution containing a precious metal;
[0096] (6) adding the substance obtained in step (4) to the impregnation solution of the precious metal obtained in step (5), impregnating at 25° C. for 2 h, and then placing it in a rotary evaporation container and drying it at 120° C. for 2 h;
[0097] (7) The material obtained in step (6) was placed in a muffle furnace, calcined at 450°C for 3 h, and then reduced in a tubular furnace at 400°C for 4 h under hydrogen conditions to obtain catalyst S1;
[0098] The distribution position and content of each substance in the catalyst S1 are shown in Table 1.
[0099] Example 2
[0100] The preparation method is the same as that of Example 1, except that in step (5), the amount of palladium nitrate solution (concentration of 18.56 wt%) added is 0.27 g. Finally, catalyst S2 is prepared.
[0101] The distribution position and content of each substance in the catalyst S2 are shown in Table 1.
[0102] Example 3
[0103] The preparation method is the same as that of Example 1, except that in step (5), the amount of palladium nitrate solution (concentration of 18.56 wt%) added is 0.81 g. Finally, catalyst S3 is prepared.
[0104] The distribution position and content of each substance in the catalyst S3 are shown in Table 1.
[0105] Example 4
[0106] The preparation method is the same as that of Example 1, except that in step (5), the amount of palladium nitrate solution (concentration of 18.56 wt%) added is 1.08 g. Finally, catalyst S4 is prepared.
[0107] The distribution position and content of each substance in the catalyst S4 are shown in Table 1.
[0108] Example 5
[0109] The preparation method is the same as that of Example 1, except that in step (5), the amount of palladium nitrate solution (concentration of 18.56 wt%) added is 2.16 g. Finally, catalyst S5 is prepared.
[0110] The distribution position and content of each substance in the catalyst S5 are shown in Table 1.
[0111] Example 6
[0112] The preparation method is the same as that of Example 1, except that in step (1), the amount of sulfuric acid is changed to 0.15 g. Finally, catalyst S6 is prepared.
[0113] The distribution position and content of each substance in the catalyst S6 are shown in Table 1.
[0114] Example 7
[0115] The preparation method is the same as that of Example 1, except that in step (1), the amount of sulfuric acid is changed to 0.94. Finally, catalyst S7 is prepared.
[0116] The distribution position and content of each substance in the catalyst S7 are shown in Table 1.
[0117] Example 8
[0118] The preparation method is the same as that of Example 1, except that in step (1), the amount of sulfuric acid is changed to 1.57 g. Finally, catalyst S8 is prepared.
[0119] The distribution position and content of each substance in the catalyst S8 are shown in Table 1.
[0120] Example 9
[0121] The preparation method is the same as that of Example 1, except that in step (1), 0.47 g of sulfuric acid is replaced with 0.54 g of phosphoric acid. Finally, catalyst S9 is prepared.
[0122] The distribution position and content of each substance in the catalyst S9 are shown in Table 1.
[0123] Example 10
[0124] The preparation method is the same as that of Example 1, except that in step (1), the amount of chromium nitrate nonahydrate is changed to 13.48 g. Finally, catalyst S10 is prepared.
[0125] The distribution position and content of each substance in the catalyst S10 are shown in Table 1.
[0126] Embodiment 11
[0127] The preparation method is the same as that of Example 1, except that in step (1), the amount of chromium nitrate nonahydrate is changed to 23.1 g. Finally, catalyst S11 is prepared.
[0128] The distribution position and content of each substance in the catalyst S11 are shown in Table 1.
[0129] Example 12
[0130] The preparation method is the same as that of Example 1, except that in step (1), 7.7 g of chromium nitrate nonahydrate is replaced by 3.7 g of Mn(NO3)2.4H2O. Finally, catalyst S12 is prepared.
[0131] The distribution position and content of each substance in the catalyst S12 are shown in Table 1.
[0132] Embodiment 13
[0133] The preparation method is the same as that of Example 1, except that in step (1), 7.7 g of chromium nitrate nonahydrate is replaced by 7.4 g of Mn(NO3)2.4H2O. Finally, catalyst S13 is prepared.
[0134] The distribution position and content of each substance in the catalyst S13 are shown in Table 1.
[0135] Embodiment 14
[0136] The preparation method is the same as that of Example 1, except that in step (1), 7.7 g of chromium nitrate nonahydrate is replaced by 12 g of Mn(NO3)2.4H2O. Finally, catalyst S14 is prepared.
[0137] The distribution position and content of each substance in the catalyst S14 are shown in Table 1.
[0138] Embodiment 15
[0139] The preparation method is the same as that of Example 1, except that in step (4), the concentration of the pseudo-boehmite slurry is 14.5wt% and the thickness of the alumina coating layer is 0.2mm. Finally, catalyst S15 is prepared.
[0140] The distribution position and content of each substance in the catalyst S15 are shown in Table 1.
[0141] Example 16
[0142] The preparation method is the same as that of Example 1, except that in step (4), the concentration of pseudo-boehmite is 23.2 wt % and the thickness of the alumina coating layer is 0.3 mm. Finally, catalyst S16 is prepared.
[0143] The distribution position and content of each substance in the catalyst S16 are shown in Table 1.
[0144] Embodiment 17
[0145] The preparation method is the same as that of Example 1, except that in step (4), the concentration of pseudo-boehmite is 33 wt % and the thickness of the alumina coating layer is 0.4 mm. Finally, catalyst S17 is prepared.
[0146] The distribution position and content of each substance in the catalyst S17 are shown in Table 1.
[0147] Embodiment 18
[0148] The preparation method is the same as that of Example 1, except that in step (1), the amount of nickel nitrate hexahydrate is changed to 32.8 g. Finally, catalyst S18 is prepared.
[0149] The distribution position and content of each substance in the catalyst S18 are shown in Table 1.
[0150] Comparative Example 1
[0151] The preparation method is the same as in Example 1, except that:
[0152] In step (1), chromium nitrate nonahydrate and sulfuric acid are not added, and only 39.64 g of nickel nitrate hexahydrate is added to deionized water;
[0153] In step (2), the amount of alumina carrier added is 42 g;
[0154] Instead of performing steps (4) to (7), the catalyst core obtained in step (3) was placed in a tubular furnace and reduced at 400° C. for 4 h under hydrogen conditions to obtain catalyst D1.
[0155] Comparative Example 2
[0156] (1) adding 1.62 g of a palladium nitrate solution having a concentration of 18.56 wt % to deionized water to obtain an impregnation solution;
[0157] (2) at 70°C, 40.2 g of an alumina carrier with a diameter of 3 mm and 50 mL of pseudo-boehmite slurry (concentration of 10.5 wt%) were contacted in a blower coater for 30 min to coat the surface of the alumina carrier with pseudo-boehmite, and then calcined at 450°C for 4 h, so that the surface of the alumina carrier was coated with an alumina coating layer with a thickness of 0.15 mm;
[0158] (3) adding the impregnation solution prepared in step 1 to the product prepared in step 2, impregnating at 25°C for 2 hours, and then placing it in a rotary evaporation container and drying it at 120°C for 2 hours;
[0159] (4) The material obtained in step (3) was placed in a muffle furnace, calcined at 450°C for 3 h, and then reduced in a tubular furnace at 400°C for 4 h under hydrogen conditions to obtain catalyst D2.
[0160] Comparative Example 3
[0161] The preparation steps are the same as those of Comparative Example 2, except that in step (1), the amount of palladium nitrate solution added is 0.54 g. Catalyst D3 is obtained.
[0162] Comparative Example 4
[0163] The preparation method is the same as in Example 1, except that:
[0164] In step (1), sulfuric acid was not added, and only 39.64 g of nickel nitrate hexahydrate and 7.7 g of chromium nitrate nonahydrate were added to deionized water;
[0165] In step (2), the amount of alumina carrier added is 41 g;
[0166] Instead of performing steps (4) to (7), the catalyst core obtained in step (3) was placed in a tubular furnace and reduced at 400° C. for 4 h under hydrogen conditions to obtain catalyst D4.
[0167] Comparative Example 5
[0168] (1) dissolving 39.64 g of nickel nitrate hexahydrate, 7.7 g of chromium nitrate nonahydrate, 0.47 g of sulfuric acid and 0.54 g of 18.56 wt% palladium nitrate solution in 40 mL of deionized water to prepare an impregnation solution;
[0169] (2) at 70°C, 40.2 g of an alumina carrier having a diameter of 3 mm and 50 mL of a pseudo-boehmite slurry (with a concentration of 10.5 wt%) were contacted in a blower coater to coat the surface of the alumina carrier with the pseudo-boehmite, and then calcined at 450°C for 4 h, so that the surface of the alumina carrier was coated with an alumina coating layer with a thickness of 0.15 mm;
[0170] (3) Add the impregnation solution prepared in step 1 to the product prepared in step 2, impregnate at 25°C for 2h, then place it in a rotary evaporation container and dry it at 120°C for 2h;
[0171] (4) The material obtained in step (3) was placed in a muffle furnace, calcined at 450°C for 3 h, and then reduced in a tubular furnace at 400°C for 4 h under hydrogen conditions to obtain catalyst D5.
[0172] Test Case
[0173] Under the reaction conditions of pressure of 0.11 MPa and temperature of 220°C, the catalysts of the above-mentioned embodiment and comparative example were used respectively for 0.8 h. -1 The dehydrogenation of perhydro N-ethylcarbazole was catalyzed at a reaction volume space velocity of , and the catalyst loading amount was 100 mL. In the dehydrogenation catalytic process, other heterocyclic substances other than N-ethylcarbazole and hydrogen-containing N-ethylcarbazole were impurities, and the impurity generation amount was measured by gas chromatography as shown in Table 2.
[0174] The dehydrogenation rate of the dehydrogenation catalytic reaction is calculated using the following formula, and the results of the dehydrogenation rate are shown in Table 2:
[0175] Dehydrogenation rate (%) =
[0176] Wherein, NEC refers to N-ethylcarbazole, n1 is the molar amount of 12H-N-ethylcarbazole, n2 is the molar amount of 8H-N-ethylcarbazole, n3 is the molar amount of 4H-N-ethylcarbazole, and n4 is the molar amount of N-ethylcarbazole.
[0177] n1, n2, n3, and n4 were measured using gas chromatography.
[0178] Table 1
[0179]
[0180] Table 2
[0181]
[0182] It can be seen from the results in Table 2 that the dehydrogenation catalyst provided by the present invention with a noble metal as a shell and a non-noble metal, a co-metal and an auxiliary agent as a core has higher dehydrogenation activity and lower generation of decomposition products of the hydrogen storage carrier, which is beneficial to improving the hydrogen release efficiency of the dehydrogenation catalyst and multiple recycling of the hydrogen storage carrier, and shows excellent prospects in the dehydrogenation process in the field of organic liquid hydrogen storage.
[0183] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst, characterized in that The catalyst has a core-shell structure, including a core and an outer shell, wherein the core includes a carrier and non-precious metals, auxiliary metals and auxiliary agents loaded on the carrier, and the outer shell includes an alumina coating layer and a precious metal active component loaded on the alumina coating layer; Wherein, the non-precious metal includes Ni; The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals; The auxiliary agent is S and / or P; The VIB group metal is Cr and / or Mo; The Group VIIB metal is Mn and / or Tc; The noble metal active component is selected from at least one of Pd, Pt, Au and Ag; The carrier is selected from at least one of aluminum oxide, silicon oxide and titanium oxide; Based on the total amount of the catalyst, the content of the non-precious metal calculated by element is 5-35wt%, the content of the auxiliary metal calculated by element is 0.5-6wt%, and the content of the auxiliary agent calculated by element is 0.1-1wt%; Based on the total amount of the catalyst, the content of the noble metal active component is 0.01-0.5wt%.
2. The catalyst according to claim 1, wherein The auxiliary agent is S.
3. The catalyst according to claim 2, wherein The VIB group metal is Cr; The Group VIIB metal is Mn; The noble metal active component is Pd and / or Pt.
4. The catalyst according to claim 1, wherein The auxiliary metal is a metal element of Group VIB, and the content of the auxiliary metal in terms of element is 1-6wt% based on the total amount of the catalyst; Alternatively, the auxiliary metal is a metal element of Group VIIB, and the content of the auxiliary metal in terms of element is 0.5-5 wt % based on the total amount of the catalyst.
5. The catalyst according to claim 1, wherein Based on the total amount of the catalyst, the thickness of the alumina coating layer is 0.08-0.25 mm; The ratio of the inner core radius to the thickness of the aluminum oxide coating layer is 6.5-20:
1.
6. A method for preparing a catalyst, characterized in that: The following steps are involved: (1) impregnating a carrier with an impregnation solution containing a non-precious metal precursor, a metal promoter precursor and an additive precursor, and then drying and first calcining the carrier to obtain a core of the catalyst; (2) contacting the inner core of the catalyst obtained in step (1) with a mixed solution containing an alumina precursor, and then performing a second calcination to obtain a catalyst precursor having a core-shell structure; (3) impregnating the catalyst precursor obtained in step (2) with a mixed solution containing a noble metal active component, and performing a reduction treatment to obtain the catalyst; Wherein, the non-precious metal includes Ni; The auxiliary metal is selected from at least one of Group VIB metals and Group VIIB metals; The auxiliary agent is S and / or P; The VIB group metal is Cr and / or Mo; The Group VIIB metal is Mn and / or Tc; The noble metal active component is selected from at least one of Pd, Pt, Au and Ag; The carrier is selected from at least one of aluminum oxide, silicon oxide and titanium oxide; In step (1), the amount of the impregnation liquid containing the non-precious metal precursor, the co-metal precursor and the auxiliary agent precursor is such that, based on the total amount of the prepared catalyst, the content of the non-precious metal calculated as the element is 5-35wt%, the content of the co-metal calculated as the element is 0.5-6wt%, and the content of the auxiliary agent calculated as the element is 0.1-1wt%; The amount of the mixed liquid containing the precious metal active component is such that, based on the total amount of the prepared catalyst, the content of the precious metal active component is 0.01-0.5 wt %.
7. The preparation method according to claim 6, wherein: The auxiliary agent is S.
8. The preparation method according to claim 7, wherein: The VIB group metal is Cr; The Group VIIB metal is Mn; The noble metal active component is Pd and / or Pt.
9. The preparation method according to claim 6, wherein: The auxiliary metal is a metal element of Group VIB, and the amount of the impregnation liquid containing the non-precious metal precursor, the auxiliary metal precursor and the auxiliary agent precursor is such that the auxiliary metal content calculated as the element is 1-6wt% based on the total amount of the prepared catalyst; Or, the auxiliary metal is a metal element of Group VIIB, and the amount of the impregnation solution containing the non-precious metal precursor, the auxiliary metal precursor and the auxiliary agent precursor is such that the auxiliary metal content in terms of element is 0.5-5wt% based on the total amount of the prepared catalyst.
10. The preparation method according to claim 6, wherein: The drying conditions include: drying temperature of 80-200°C and drying time of 2-24h; The first calcination conditions include: calcination temperature of 350-600°C, calcination time of 2-12h; The second calcination conditions include: calcination temperature of 350-600°C, calcination time of 2-12h; The reduction treatment conditions include: in a hydrogen-containing atmosphere, a reduction temperature of 250-600° C., and a reduction time of 2-12 hours.
11. A catalyst obtained by the preparation method according to any one of claims 6 to 10.
12. Use of the catalyst according to any one of claims 1 to 5 and 11 in the field of hydrogen storage.
13. The use according to claim 12, wherein: The hydrogen storage field is the field of organic liquid hydrogen storage.
14. A method for dehydrogenating a hydrogen storage carrier, characterized in that: include: contacting the hydrogen storage carrier with a dehydrogenation catalyst under dehydrogenation conditions; Wherein, the dehydrogenation catalyst is the catalyst described in any one of claims 1-5 and 11.
Citation Information
Patent Citations
Preparation method of thin shell shaped noble metal catalyst
CN101491778A
Catalyst, preparation method thereof and Fischer-Tropsch method
CN101757952A
Cited By
Core-shell structure cobalt-based catalyst as well as preparation method and application thereof
CN120754867A